2021
DOI: 10.30574/gscarr.2021.8.1.0140
|View full text |Cite
|
Sign up to set email alerts
|

Response of groundnut (Arachis hypogea) to rhizobia inoculation, mineral nitrogen and inoculation amendment at the two agro ecological zones of northern Nigerian savannah

Abstract: Nitrogen is the most limiting major nutrient required by all living plants. Nitrogen fertilizer is costly and too much application of nitrogen causes detrimental effects to our ecosystem. Alternatively, the use of commercial microbial inoculants will be an alternative to chemical fertilizer for the small holder farmers in northern Nigeria. Groundnut (pea nut) was selected as a test crop for the inoculation. The experiment was conducted at Sudan savannah in Kano State and Guinea savannah in Bauchi state of Nige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The effect of inoculation with rhizobia bacteria on peanuts had a significant effect compared to treatments without inoculation [4]. The results of [5] showed that the combination of rhizobium inoculum isolated from the bean plant with 50% mineral fertilization was superior in the number of root nodes and the highest weight of the root nodes, as well as the yield increased significantly by 109.4% compared to the comparison treatment. The success of the biological fertilizer used as an inoculate added to the plant growth medium depends on the efficiency of the host organism, the ability of the organisms added to coexist with the host plant, and whether they can compete with the organisms present in the root zone in the soil [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of inoculation with rhizobia bacteria on peanuts had a significant effect compared to treatments without inoculation [4]. The results of [5] showed that the combination of rhizobium inoculum isolated from the bean plant with 50% mineral fertilization was superior in the number of root nodes and the highest weight of the root nodes, as well as the yield increased significantly by 109.4% compared to the comparison treatment. The success of the biological fertilizer used as an inoculate added to the plant growth medium depends on the efficiency of the host organism, the ability of the organisms added to coexist with the host plant, and whether they can compete with the organisms present in the root zone in the soil [6,7].…”
Section: Introductionmentioning
confidence: 99%